Rhetoric in Friday sermons - Abdul Malik, Badrol Hisham; Abdullah, Muhd Alif Redzuan; Wan Ahmad, Wan Noor Aini; Abdul, Shahrul Azzim (Human Resource Management Academic Research Society, 2023)
This study is a descriptive study using the Modern Rhetorical Theory by Enos and Brown (1993) as the basis of the study. Used content analysis method to examine the textual and contextual text. The primary focus or objective of the study is to identify the type, structure, and style of rhetoric found in Friday sermons. The results showed that all types of rhetoric that kind including narrative, descriptive, exposition, argumentative, and persuasive in Friday sermons. Based on the analysis of the structure angle, it appears that rhetoric is used in all forms of the same language in the form of words, phrases, clauses, sentences, or discourse. The analysis of the rhetorical style corner resulted in a finding that suggests that the Friday sermon using a variety of rhetorical style comparisons, linkage, and conflict recurrence may be treated as the influence listener audience. In other words, rhetoric in the Friday sermon is an important element used by the preacher to enliven the atmosphere and influence the congregation's thinking